Valor nutricional, características fermentativas e microbiológicas da silagem de sorgo BRS 658 com o uso de aditivos - Führ , Claudia Anete (2020)
The aim of this work was to evaluate the nutritional value, the fractionation of carbohydrates, the fermentative profile, aerobic stability and the population of fungi present in the forage sorghum silage BRS 658 with the use of additives. The design was completely randomized (DIC) with four replications, and seven treatments have been evaluated: sorghum silage (control); sorghum silage + microbial inoculant 0.2% of natural matter (NM); sorghum silage + 4% brown sugar NM; sorghum silage + 4% brown sugar NM + microbial inoculant 0.2% NM; sorghum silage + liquid whey at 3% of NM; sorghum silage + 3% NM liquid whey + 0.2% NM microbioal inoculant; sorghum silage + liquid whey at 3% NM + microbial inoculant 0.2% MN + 4% brown sugar NM. The sorghum was cut at 111 days after emergence, in the milky - farinaceous grain stage and ensiled in polyvinyl chloride silos, adapted with a Bunsen valve, with 10 cm in diameter and 40 cm in length. Brown sugar added to sorghum silage increased the levels of: dry matter, organic matter, fraction A + B1 of carbohydrates, soluble carbohydrates, recovery of dry matter and reduction in the levels of MM, NDF and ADF. Sorghum silage with whey + microbial inoculant increased crude protein levels. The microbial inoculation treatment + brown sugar had the lowest ammoniacal nitrogen content. The treatment whey + brown sugar + microbial inoculant promoted greater specific mass. The use of brown sugar as an additive in forage sorghum silage BRS 658, contributed to improve the nutritional value by increasing the levels of dry matter, organic matter, total carbohydrates and fraction A + B1 and decreasing the levels of mineral matter, neutral detergent fiber and acid detergent fiber. The use of microbial inoculant + brown sugar in the sorghum silage BRS 658 decreased the levels of ammoniacal nitrogen, pH and propionic acid. In all treatments, there was no break in the aerobic stability of the silages. Brown sugar was the additive that showed improvement in some parameters related to nutritional value and fermentative profile.